PENGARUH ENTREPRENEURIAL LEADERSHIP DAN ENTREPRENEUR’S PASSION TERHADAP PERFORMA KERJA KARYAWAN PERUSAHAAN INDUSTRI PANGAN DI INDONESIA - Laurent, Ellisa; Efrata, Tommy (Universitas Ciputra Surabaya, 2023)
Abstract: One of the causes of decreased employee performance is a lack of leadership or entrepreneurial style. Entrepreneurial role is very important to implement in entrepreneurship because it is one of the keys to success in the company. The entrepreneurs in this study are Entrepreneurial leadership and entrepreneur's passion which have a considerable influence on employee performance and influence the company's success in achieving the goals set by supporting the human resources in the company. This research was conducted to determine the effect of entrepreneurial leadership and entrepreneur's passion on employee work performance and the effect of entrepreneurial leadership on entrepreneur's passion. Collecting research data distributed 203 questionnaires to respondents who are employees of food industry companies in Indonesia at the middle management to upper management levels. This study uses non-probability sampling, with a purposive sampling method. The data analysis technique used in this study is Smart-PLS 3.0 software with the Structural Equation Model (SEM) - Partial Least Square (PLS) method. Based on the results of this study, shows that Entrepreneurial Leadership has a significant influence on Entrepreneur's Passion, Entrepreneurial Leadership has a significant influence on Work Performance, and Entrepreneur's Passion has a significant influence on work performance.